as we can see the grap that hthe roots of the quadratic are:
x1 = 3 and x2 = 3
The graph touch x axis at with y = 0 , so we got the roots in a twin roots number that is x = 3
Now, we can write our function for the quadratic as follows
f(x) = ( x - x1 ) ( x - x2 )
f(x) = ( x - 3 ) ( x - 3 )
f(x) = ( x - 3 ) ^2
f(x) = x^2 - 3x - 3x + 9
f(x) = x^2 - 6x + 9
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?